LDIP cooperates with SEIPIN and LDAP to facilitate lipid droplet biogenesis in Arabidopsis. Issue 9 (9th June 2021) - Pyc, Michal; Gidda, Satinder K.; Seay, Damien; Esnay, Nicolas; Kretzschmar, Franziska K.; Cai, Yingqi; Doner, Nathan M.; Greer, Michael S.; Hull, J. Joe; Coulon, Denis; Bréhélin, Claire; Yurchenko, Olga; et al.
Abstract: Cytoplasmic lipid droplets (LDs) are evolutionarily conserved organelles that store neutral lipids and play critical roles in plant growth, development, and stress responses. However, the molecular mechanisms underlying their biogenesis at the endoplasmic reticulum (ER) remain obscure. Here we show that a recently identified protein termed LD-associated protein [LDAP]-interacting protein (LDIP) works together with both endoplasmic reticulum-localized SEIPIN and the LD-coat protein LDAP to facilitate LD formation in Arabidopsis thaliana . Heterologous expression in insect cells demonstrated that LDAP is required for the targeting of LDIP to the LD surface, and both proteins are required for the production of normal numbers and sizes of LDs in plant cells. LDIP also interacts with SEIPIN via a conserved hydrophobic helix in SEIPIN and LDIP functions together with SEIPIN to modulate LD numbers and sizes in plants. Further, the co-expression of both proteins is required to restore normal LD production in SEIPIN -deficient yeast cells. These data, combined with the analogous function of LDIP to a mammalian protein called LD Assembly Factor 1, are discussed in the context of a new model for LD biogenesis in plant cells with evolutionary connections to LD biogenesis in other eukaryotes. Abstract : The lipid droplet (LD) proteins LDIP and LDAP cooperate with endoplasmic reticulum-localized SEIPIN to coordinate LD formation in plant cells.